Development of Flipbook with Living Value Education Program-Based as Teaching Materials to Improve Students' Religious Values - Nada, Damai Ikhsa; Apriani, An-Nisa; Sari, Indah Perdana; Ariyani, Yusinta Dwi (Universitas Muhammadiyah Yogyakarta, 2024)
The current use of technology-based learning media is still limited to textbooks from the government and projectors that display presentation slides or videos. The current study used a flipbook as a new alternative for teaching materials with additional religious values. This study aimed to 1) generate a flipbook for social and science studies (Ilmu Pengetahuan Alam dan Sosial or IPAS) with living values education program-based feasible to improve religious values; 2) determine the responses about the IPAS flipbook as a learning material from the teachers; 3) evaluate the responses about the IPAS flipbook as a learning material from the teachers from the students in enhancing their religious characteristics. The research design used was a research-and-development with a 4D research and development model (define, design, development, and dissemination). The subjects of the validation test are material experts and media experts, while the responders to the media are teachers and 19 fourth-grade students of SD IT Samawi. The data was collected using interviews, observations, and questionnaires. The data analysis methods used are qualitative and quantitative. The results showed that the feasibility assessment of the IPAS flipbook is categorized as having